Management consultants - Macdonald, Stuart (Henry Stewart Talks, 2010)
Change in organisations often means bringing in management consultants, Managers may have little choice, Failure to hire consultants suggests that managers are less than serious about change, Yet, expectations are raised when the consultants arrive, especially if they are expensive consultants, How managers can become dependent on management consultants and their methods